Feel-Bad Euro Noir : Imagining Europe from its Eastern Edge in the Polish HBO TV series The Border / Wataha. - Mrozewicz, Anna (Palgrave Studies in European Communication Research and Education, 2025)
This chapter explores the HBO-produced Polish television series The Border (Wataha, 2014-2019). The series is examined as an example of what can be termed feel-bad Euro-noir. The analysis delves into the complex use of locations, particularly the Bieszczady Mountains, and the depiction of the Polish-Ukrainian border – marking the eastern edge of the European Union. These settings are dissected for their layered portrayal, showing how they draw on entrenched stereotypes in Polish cultural imagination whilst also serving as a bleak metaphor for contemporary Europe. The chapter combines an aesthetic and narrative examination of the series’ spatial representation with an analysis of the political and media-political context within Poland, informed by a 2019 interview with the scriptwriter and showrunner, Artur Kowalewski (2019). The analysis demonstrates how The Border saturates its settings with grim recollections of Europe’s troubled past and unsettling depictions of nature, deliberately avoiding catharsis to create a deeply disquieting, ‘feel-bad’ experience (Lübecker 2015). Moreover, the chapter investigates how the series’ implied audience expands from a national focus in the first season to a European and transnational scope in the second. This broadening of focus enhances the series’ socio-political relevance, particularly in light of Europe’s current geopolitical challenges.
Keywords: Euro-noir; Polish television; Spatial representation; Environmental imagination; Borderlands; HBO